Penerapan Sistem Pakar Penanggulangan Hama dan Penyakit Pada Tanaman Cabai Menggunakan Metode Forward Chaining ( Studi Kasus SMK-PP N Jambi ) - Louis, Ahmad (JURNAL AKADEMIKA, 2016)
Agriculture has an important meaning for human life, for human life, for it also agriculture will still be there. The chili is made from the farm where each year the demand for pepper is growing because of the human population continues to grow. In particular, this plant is the result of farming used as a food flavoring. It is often the case, many of the losses caused by the plant diseases to be diagnosed late and already reached a severe and lead to crop failure.